1976
DOI: 10.1002/cpt1976193339
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of procainamide in normal and cardiac subjects

Abstract: Since the publication by Dreyfuss and associates 4 , 5 in which N-acetylprocainamide (NAP A) was found as a metabolite of procainamide (PA), a number of reports have appeared in the literature on the metabolism of procainamide. 6 , 12, 13, 17 These have also indicated the amount of NAPA in the plasma and urine of normal volunteers and patients. Graffner, Johnsson, and Sjogren 13 studied 4 normal volunteers and, after a single oral dose of PA -3H or after the administration of sustainedrelease preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Giardina et al 20) reported that 31-56%, 7-24%, and less than 0.2% of the dose were excreted as procainamide, N-acetylprocainamide, and p-aminobenzoic acid, respectively, in 24 h after a single oral dosing of 14 C-labeled procainamide to patients with cardiac disease. Therefore, the results of the present in vitro study, using human liver microsomes and cytosol, are consistent with the in vivo clinical studies, which demonstrated that N-acetylprocainamide is a predominant metabolite after oral dosing of procainamide to humans, whereas hydrolyzed metabolites such as p-aminobenzoic acid are minor metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giardina et al 20) reported that 31-56%, 7-24%, and less than 0.2% of the dose were excreted as procainamide, N-acetylprocainamide, and p-aminobenzoic acid, respectively, in 24 h after a single oral dosing of 14 C-labeled procainamide to patients with cardiac disease. Therefore, the results of the present in vitro study, using human liver microsomes and cytosol, are consistent with the in vivo clinical studies, which demonstrated that N-acetylprocainamide is a predominant metabolite after oral dosing of procainamide to humans, whereas hydrolyzed metabolites such as p-aminobenzoic acid are minor metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results of the present in vitro study, using human liver microsomes and cytosol, are consistent with the in vivo clinical studies, which demonstrated that N-acetylprocainamide is a predominant metabolite after oral dosing of procainamide to humans, whereas hydrolyzed metabolites such as p-aminobenzoic acid are minor metabolites. 20) Recently, human hepatocytes, containing both microsomal and cytosolic enzymes, were reported to be useful for the prediction of hepatic clearance of compounds, which are metabolized through several kinds of metabolic pathways, including phase I and phase II reactions. 9,21) Further studies using hepatocytes might be required to improve the quantitative prediction of the hepatic clearance.…”
Section: Discussionmentioning
confidence: 99%
“…That ethanol administration prior to procainamide intake did not markedly influence the procainamide bioavailability over the first 2 h (Table 4), may again be due to the lack of first-pass procainamide elimination by acetylation (Table 1), since any alteration in the rate of a firstpass reaction would affect bioavailability markedly (Shand & Turner, 1978). Thus another metabolic pathway (Graffner et al, 1975;Giardina et al, 1976) uninfluenced by acetylator phenotype or ethanol could be responsible for a possible first-pass metabolism of procainamide. Finally, the magnitude of the percentage N-acetylprocainamide excreted in urine (Table 3) may also argue against a first-pass elimination of procainamide by N-acetylation. …”
Section: Discussionmentioning
confidence: 99%
“…Ae (duSouich & Erill, 1977;Giardina et al, 1976), desethylprocainamide (Ruo etal., 1981) and their acetylated forms. The extent to which a drug is excreted in the urine is a function of its urinary excretion rate constant relative to the rate constants governing its elimination by other routes.…”
Section: Effect Of Ranitidine On Procainamide Dispositionmentioning
confidence: 99%